Calibrated Analytical Model of Low Cost YL-69 Hygrometer Sensor for Determining Moisture Content of Fruit and Vegetable Waste - Jessie, Rose; Jia Chi, Lai; Yi Lung, Then; Chamath Kanalaka, Vithanawasam (2020)
Moisture content (MC) is one of the influential parameters in food waste composting process. With the use of low aeration rate in achieving minimal loss of moisture, 60% moisture content is found to be the optimum indicator. There is a need to retain moisture of the composting process at this set point to achieve peak temperature while eliminating odour emission. A low cost YL-69 hygrometer sensor which has been verified for its applicability in measuring volumetric content of soil was used in this investigation. The sensor measured moisture content of food waste composting process continuously. With this, two models were developed, and standard soil gravimetric method showed a strong relationship of R2 is 0.962 with error 5.02 % (<; 10%). The application of YL-69 hygrometer sensor for measurement of moisture content in food waste composting process is thus appropriate.